GmVTL1a is an iron transporter on the symbiosome membrane of soybean with an important role in nitrogen fixation - Brear, Ella M.; Bedon, Frank; Gavrin, Aleksandr; Kryvoruchko, Igor S.; Torres-Jerez, Ivone; Udvardi, Michael K.; Day, David A.; Smith, Penelope M. C. (The New phytologist, 2020)
Legumes establish symbiotic relationships with soil bacteria (rhizobia), housed in nodules on roots. The plant supplies carbon substrates and other nutrients to the bacteria in exchange for fixed nitrogen. The exchange occurs across a plant-derived symbiosome membrane (SM), which encloses rhizobia to form a symbiosome. Iron supplied by the plant is crucial for rhizobial enzyme nitrogenase that catalyses nitrogen fixation, but the SM iron transporter has not been identified. We use yeast complementation, real-time PCR and proteomics to study putative soybean (Glycine max) iron transporters GmVTL1a and GmVTL1b and have characterized the role of GmVTL1a using complementation in plant mutants, hairy root transformation and microscopy. GmVTL1a and GmVTL1b are members of the vacuolar iron transporter family and homologous to Lotus japonicus SEN1 (LjSEN1), which is essential for nitrogen fixation. GmVTL1a expression is enhanced in nodule infected cells and both proteins are localized to the SM. GmVTL1a transports iron in yeast and restores nitrogen fixation when expressed in the Ljsen1 mutant. Three GmVTL1a amino acid substitutions that block nitrogen fixation in Ljsen1 plants reduce iron transport in yeast. We conclude GmVTL1a is responsible for transport of iron across the SM to bacteroids and plays a crucial role in the nitrogen-fixing symbiosis.